A study of the influence of workplace ostracism on employees' performance: moderating effect of perceived organizational support - Youngkeun Choi (European Journal of Management and Business Economics (EJM&BE), 2020)
Purpose Based on the conservation of resource theory, this study developed and tested the relationship between workplace ostracism and job performance. And it assumes that the direct link between workplace ostracism and supervisor-rated in-role performance/organizational citizenship behavior is moderated by perceived organizational support. Design/methodology/approach For this, this study used a survey method and multiple regression analyses with multisource data from 256 Korean employees and their supervisors. Findings The results suggest the following. First, workplace ostracism was negatively associated with supervisor-rated in-role performance and organizational citizenship behaviors. Second, there was a stronger negative relationship between workplace ostracism and supervisor-rated in-role performance/organizational citizenship behaviors for employees with low as opposed to those with high levels of perceived organizational support. Originality/value This study is the first one to examine the moderating effect of perceived organizational support on the relationship between workplace ostracism and supervisor-rated in-role performance/organizational citizenship behavior.
Keywords: 650; Workplace ostracism; In-role performance; Organizational citizenship behavior; Perceived organizational support